The effects of government capital and liquidity support programs on bank lending: Evidence from the syndicated corporate credit market - Wu, Deming (Journal of Financial Stability, 2015)
This study jointly evaluates the effects of the U.S. Treasury's Troubled Asset Relief Program (TARP), the Federal Reserve's Discount Window (DW), and Term Auction Facility (TAF) on bank syndicated lending during the 2007–2009 financial crisis, using a unique data set that tracks the exposure of each lender in each syndicated credit facility in each year. By comparing lending changes within a group of banks that lend to the same facility of the same firm in the same year, it eliminates the impacts of demand-side factors that often bias the results of empirical studies on bank credit supply. Overall, I find that TARP, DW, and TAF played only a marginal role in increasing bank syndicated lending. By examining lending changes at the facility-lender and firm-lender levels, this study is less prone to the reverse causality problem that is inherent in studies using bank-level data. Therefore, this study complements studies using bank-level data and provides policymakers with a balanced view on the effects of these programs.